2015
DOI: 10.1038/cgt.2015.21
|View full text |Cite
|
Sign up to set email alerts
|

The receptor for advanced glycation end products (RAGE) enhances autophagy and neutrophil extracellular traps in pancreatic cancer

Abstract: Neutrophil extracellular traps (NETs) are formed when neutrophils expel their DNA, histones and intracellular proteins into the extracellular space or circulation. NET formation is dependent on autophagy and is mediated by citrullination of histones to allow for unwinding and subsequent expulsion of DNA. NETs play an important role in the pathogenesis of several sterile inflammatory diseases, including malignancy, therefore we investigated the role of NETs in the setting of pancreatic ductal adenocarcinoma (PD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
139
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 144 publications
(156 citation statements)
references
References 63 publications
6
139
0
Order By: Relevance
“…Interestingly, in addition to its role in the internalization of NETs, RAGE activation is also a trigger for NETosis. 46 In addition to its role in the induction of EndMT, the degradation of VE-cadherin by NET-associated elastase also caused a rapid phase of increased vascular permeability, as demonstrated by transendothelial albumin passage assays. Because the integrity of intercellular junctions, mediated particularly through VE-cadherin, is a prerequisite for maintaining a restrictive endothelial barrier, 47,48 NETs may thus play a role in the development of edema and proteinuria by increasing .…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, in addition to its role in the internalization of NETs, RAGE activation is also a trigger for NETosis. 46 In addition to its role in the induction of EndMT, the degradation of VE-cadherin by NET-associated elastase also caused a rapid phase of increased vascular permeability, as demonstrated by transendothelial albumin passage assays. Because the integrity of intercellular junctions, mediated particularly through VE-cadherin, is a prerequisite for maintaining a restrictive endothelial barrier, 47,48 NETs may thus play a role in the development of edema and proteinuria by increasing .…”
Section: Discussionmentioning
confidence: 99%
“…To date, one other study has described a NET mechanism that exhibited both rapid and ROS-independent mechanism of NET release, which was induced by the Gram-positive bacteria Staphylococcus aureus [37]. Furthermore, Boone, et al [40] have recently studied NETs in PaCa in vivo, and reported that NETs released in PaCa are mediated through autophagy pathways. Specifically, the receptor for advanced glycation end products (RAGE) which mediates autophagy in PaCa was found to be necessary for NET release, as neutrophils from RAGE knockout mice were less prone to release NETs.…”
Section: Discussionmentioning
confidence: 99%
“…NETs have been observed in both murine and human tumors: sarcomas, pancreatic adenocarcinoma and LLC lung carcinomas [11][12][13][14] and have been shown to promote metastasis following septicemia in mice. 15 To evaluate if the presence of PAD4/ NETs in the host affects primary tumor growth, we compared tumor progression in WT mice to PAD4-deficient mice whose neutrophils are defective in NET formation.…”
Section: Presence Of Nets Increases Lewis Lung Carcinoma (Llc) Tumor mentioning
confidence: 99%